Determination of heavy metals and morphoanatomical characteristics of the monocots Aristida mutabilis and Cenchrus ciliaris in the dust-contaminated stone crushing industry of Sargodha, Pakistan - Muhammad Asim Sultan; Iftikhar Ahmad; Muhammad Arif; Saud Alamri; Manzer H Siddiqui; Saima Sadaf; Muhammd Kamran (Environmental Monitoring and Assessment, 2025)

Cadmium (Cd) detoxification and activation of plant defense enzymes in wheat (Triticum aestivum) through the use of endophytic Bacillus thuringiensis and Salix alba root powder - Asim Shahzad; Sofia Hameed; Mingzhou Qin; Haoyang Li; Sadia Zafar; Samina Siddiqui; Shehla Sattar; Zahid Mahmood; Shaila Mehwish (Environmental Pollution, 2025)

Folate decorated chitosan-chondroitin sulfate nanoparticles loaded hydrogel for targeting macrophages against rheumatoid arthritis - Bazla Siddiqui; Asim ur Rehman; Rabia Gul; Iqra Chaudhery; Kifayat Ullah Shah; Naveed Ahmed (Carbohydrate Polymers, 2024)

Exploiting Recent Trends in the Treatment of Androgenic Alopecia through Topical Nanocarriers of Minoxidil - Khushbakht Saleem; Bazla Siddiqui; Asim .ur.Rehman; Malik Mumtaz Taqi; Naveed Ahmed (AAPS PharmSciTech, 2022)

Geological and petrographic investigations of the Miocene Molasse deposits in Sub-Himalayas, District Sudhnati, Pakistan - Asim Javed; Ali Wahid; Muhammad Saleem Mughal; Muhammad Sabir Khan; Raja Saad Qammar; Syed Haroon Ali; Numair Ahmad Siddiqui; Muhammad Atif Iqbal (Arabian Journal of Geosciences, 2021)

Hydrocarbon degradation in oily sludge by bacterial consortium assisted with alfalfa (Medicago sativa L.) and maize (Zea mays L.) - Asim Shahzad; Samina Siddiqui; Asghari Bano; Shehla Sattar; Muhammad Zaffar Hashmi; Mingzhou Qin; Abdul Shakoor (Arabian Journal of Geosciences, 2020)

Antiplatelet activity, molecular docking and QSAR study of novel N′-arylmethylidene-3-methyl-1-phenyl-6-p-chlorophenyl-1H-pyrazolo[3,4-b] pyridine-4-carbohydrazides - Ayesha Ramzan; Sara Siddiqui; Ahmad Irfan; Abdullah G. Al-Sehemi; Aftab Ahmad; Francis Verpoort; Adeel H. Chughtai; Misbahul A. Khan; Munawar A. Munawar; Muhammad Asim Raza Basra (Medicinal Chemistry Research, 2018)

Seismic attributes’ application to evaluate the Goru clastics of Indus Basin, Pakistan - Muhammad Naseer Tayyab; Shazia Asim; Muhammad Mass Siddiqui; Muhammad Naeem; Sarfraz Hussain Solange; Farhan Khan Babar (Arabian Journal of Geosciences, 2017)

Identification of the deleterious 2080insA BRCA1 mutation in a male renal cell carcinoma patient from a family with multiple cancer diagnoses from Pakistan - Muhammad U. Rashid; Sidra Gull; Saima Faisal; Saba Khaliq; Kashif Asghar; Neelam Siddiqui; Asim Amin; Ute Hamann (Familial Cancer, 2011)

Suppression of NFκB and its Regulated Gene Products by Oral Administration of Green Tea Polyphenols in an Autochthonous Mouse Prostate Cancer Model - Imtiaz A. Siddiqui; Yogeshwer Shukla; Vaqar M. Adhami; Sami Sarfaraz; Mohammad Asim; Bilal Bin Hafeez; Hasan Mukhtar (Pharmaceutical Research, 2008)

Genomics of hybrid poplar ( Populus trichocarpa × deltoides ) interacting with forest tent caterpillars ( Malacosoma disstria ): normalized and full‐length cDNA libraries, expressed sequence tags, and a cDNA microarray for the study of insect‐induced defences in poplar - STEVEN RALPH; CLAIRE ODDY; DAWN COOPER; HESTHER YUEH; SHARON JANCSIK; NATALIA KOLOSOVA; RYAN N. PHILIPPE; DANA AESCHLIMAN; RICK WHITE; DEZENE HUBER; CAROL E. RITLAND; FRANÇOIS BENOIT; et al. (Molecular Ecology, 2006)
As part of a genomics strategy to characterize inducible defences against insect herbivory in poplar, we developed a comprehensive suite of functional genomics resources including cDNA libraries, expressed sequence tags (ESTs) and a cDNA microarray platform. These resources are designed to complement the existing poplar genome sequence and poplar ( Populus spp.) ESTs by focusing on herbivore‐ and elicitor‐treated tissues and incorporating normalization methods to capture rare transcripts. From a set of 15 standard, normalized or full‐length cDNA libraries, we generated 139 007 3′‐ or 5′‐end sequenced ESTs, representing more than one‐third of the c. 385 000 publicly available Populus ESTs. Clustering and assembly of 107 519 3′‐end ESTs resulted in 14 451 contigs and 20 560 singletons, altogether representing 35 011 putative unique transcripts, or potentially more than three‐quarters of the predicted c. 45 000 genes in the poplar genome. Using this EST resource, we developed a cDNA microarray containing 15 496 unique genes, which was utilized to monitor gene expression in poplar leaves in response to herbivory by forest tent caterpillars ( Malacosoma disstria ). After 24 h of feeding, 1191 genes were classified as up‐regulated, compared to only 537 down‐regulated. Functional classification of this induced gene set revealed genes with roles in plant defence (e.g. endochitinases, Kunitz protease inhibitors), octadecanoid and ethylene signalling (e.g. lipoxygenase, allene oxide synthase, 1‐aminocyclopropane‐1‐carboxylate oxidase), transport (e.g. ABC proteins, calreticulin), secondary metabolism [e.g. polyphenol oxidase, isoflavone reductase, (–)‐germacrene D synthase] and transcriptional regulation [e.g. leucine‐rich repeat transmembrane kinase, several transcription factor classes (zinc finger C3H type, AP2/EREBP, WRKY, bHLH)]. This study provides the first genome‐scale approach to characterize insect‐induced defences in a woody perennial providing a solid platform for functional investigation of plant–insect interactions in poplar.